2015
DOI: 10.3109/00016489.2015.1052983
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery for the management of head and neck squamous cell carcinoma of unknown primary

Abstract: The primary tumour was identified by TORS in seven of the 13 patients (54%) at the lingual tonsils. Human papillomavirus DNA and p16 were positive in all identified primary tumour specimens and in the corresponding lymph node metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…In patients who had undergone tonsillectomy and random biopsies, the HPV prevalence was lower (28-52%) (17). Furthermore, the application of robotic surgery to the diagnostic work-up of patients classified as CUP, comprising the removal of lymphoid tissue localised superficially in the base of the tongue, has showed promising results and improvement of the detection rate of the primary tumours (8). Thus, a variation in HPV prevalence in CUP of the head and neck region is to be expected, depending on the diagnostic procedure; furthermore, HPV prevalence differs widely for OPSCC between countries and over time (1,(5)(6)(7).…”
Section: Cup Of the Head And Neck Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who had undergone tonsillectomy and random biopsies, the HPV prevalence was lower (28-52%) (17). Furthermore, the application of robotic surgery to the diagnostic work-up of patients classified as CUP, comprising the removal of lymphoid tissue localised superficially in the base of the tongue, has showed promising results and improvement of the detection rate of the primary tumours (8). Thus, a variation in HPV prevalence in CUP of the head and neck region is to be expected, depending on the diagnostic procedure; furthermore, HPV prevalence differs widely for OPSCC between countries and over time (1,(5)(6)(7).…”
Section: Cup Of the Head And Neck Regionmentioning
confidence: 99%
“…de-escalated RT and chemotherapy, or for minimal invasive surgery, such as robotic surgery (1,8,9). In addition, attention has been directed towards identifying HPV at other head and neck sites.…”
Section: Introductionmentioning
confidence: 99%
“…TOLM alone has enhanced occult tumour detection rates following lingual tonsillectomy of 61%-68% [8,30] versus 51%-100% for TORS lingual tonsillectomy [28,[31][32][33][34][35][36]. Compared to TOLM lingual tonsillectomy, TORS has the added advantage of superior three-dimensional (3D) high-definition visualisation, wider range of instrument motion with seven degrees of freedom plus the ability to manoeuvre around corners with the help of angled scopes, significant reduction in hand tremors, decreased fatigue, and improved hand-eye coordination [35,37].…”
Section: Tolm Versus Tors Lingual Tonsillectomymentioning
confidence: 99%
“…According to Durmus et al [41] the PT was identified in 77% of patients (17 of 22) with 80% HPV-positive LNM residing in the palatine tonsil in 59% (13 of 22), and the BOT in 18% (4 of 22). In a study by Channir et al [42] the PT was identified by TORS in 7/13 patients (54%) at the lingual tonsils with HPV-positive LNM in all of these patients.…”
Section: Discussionmentioning
confidence: 99%